Investigating the Effects of Heating Rate and Granulation on Extracted Oil-Shale using Microwaves and Conventional Heating Methods - Hassan Naderi; Ali Shekarifard; Jaber Taheri shakib (Journal of Petroleum Science and Technology)
The quality and extraction rate of oil shale is a significant challenge in the oil shale processing field. In this article, the effects of heating rate and grain size as fundamental parameters in oil shale production from the QaliKuh reservoir in Iran on the quantity and quality of produced oil shale are explored as other sources. Fisher’s developed microwaves at 2450 kHz were used to heat several oil shale samples at power levels of 650, 900, and 1200 watts up to coking temperature (700 °C). It was observed that the amount of oil produced increased from 5.2% to 5.9%, then it reduced to 5% weight of the sample as the microwave heating rate increased; however, the quality of the oil (asphaltene reduced from 25% to 19%, sulfur content reduced from 16% to 7%, and carbon percentage increased from 67% to 78%,) improved. In contrast, conventional oil shale pyrolysis showed that the quality of the oil improved with an increase in the heating rate (asphaltene reduced from 31% to 28 %,  sulfur content reduced from 19% to 13%, and carbon percentage near to constant), while the amount of produced oil diminished from 4.7% to 4.3% weight of the sample. The grain size of the shale was divided into three ranges: 7-12 mm, 7-4 mm, and less than 4 mm. In the case of microwave heating, the amount of produced oil increased with the grain size reduction (from 5.9% to 6.8% weight of the sample). Still, the quality fluctuated (asphaltene reduced from 20% to 18 % then increased to 22%,  sulfur content reduced from 12% to 10% then increased to 15%, carbon content increased from 75% to 80% then reduced to 69%, Aliphatic component increased from 38% to 40.5% then reduced to 34%, also aromatic index reduced from 0.28% to 0.26% then increased to 0.31%). These results suggest that there is potential for further research to optimize the grain size for oil shale production. With the conventional heating techniques, the quality of the produced oil improved but can also fluctuate with decreases in grain size (from 4.7% to 5.4% then 5.1%). Also, the quality fluctuated (asphaltene reduced from 31% to 30 % then increased to 33%,  sulfur content reduced from 19% to 17% then increased to 20%, carbon content increased from 62% to 71% then reduced to 64%, Aliphatic component increased from 28% to 30% then reduced to 25%, also aromatic index reduced from 0.29%, to 0.42% then increased to 0.36%). It was found that microwave pyrolysis yielded more oil produced than the conventional method and improved the quality of the oil. An optimal particle size and heating rate can be established based on the results, sparking interest in further research to explore these possibilities.